Corrosion inhibition by benzotriazole derivatives and sodium dodecyl sulphate as corrosion inhibitors for copper in ground water at different temperatures. (10th March 2015) - Gopi, D.; Sherif, El‐Sayed M.; Surendiran, M.; Angeline Sakila, D. M.; Kavitha, L.
<x xml:space="preserve">Abstract</x> 1‐(2‐Pyrrole carbonyl) benzotriazole (PBTA) and 1‐(2‐thienyl carbonyl)‐benzotriazole (TBTA) were synthesized. Different concentrations of PBTA, TBTA, sodium dodecyl sulphate (SDS), and molybdate (Mo) were evaluated as corrosion inhibitors for copper in ground water medium at different temperatures. The obtained results were compared with the effect of benzotriazole (BTA) on the inhibition of copper corrosion at the same condition. The study was performed using potentiodynamic polarization, electrochemical impedance spectroscopy, cyclic voltammetry, and scanning electron microscopy investigations. A good inhibition is ensured at elevated temperatures. All measurements indicated that PBTA, TBTA, and BTA act as good corrosion inhibitors and their inhibition efficiency (IE%) increased with combining them with optimum concentration of SDS and Mo. Furthermore, the best performance was recorded for the compound PBTA + SDS + Mo, which was found to offer increased IE% in a synergistic manner, thereby acting as a good corrosion inhibitor for copper in ground water medium. Copyright © 2015 John Wiley & Sons, Ltd.